A Cross-Disciplinary Exploration of Entrepreneurship Research - Duane Ireland, R.; Webb, Justin W. (Journal of Management, 2007)
The eclectic and pervasive benefits of entrepreneurship are generating research questions that interest scholars in a variety of disciplines. These questions have been primarily examined within the context of a scholar's home discipline while ignoring insights from other disciplines. This approach has left entrepreneurship research as a widely dispersed, loosely connected domain of issues. In this review, the authors explore entrepreneurship research in accounting, anthropology, economics, finance, management, marketing, operations management, political science, psychology, and sociology. They seek to identify common interests that can serve as a bridge for scholars interested in using a multitheoretic and multimethodological lens to design and complete entrepreneurship studies.